A Comparison of Primary Mathematics Curriculum of Bangladesh and West Bengal of India – Why? - HALIM, MD. ABDUL (SCHOOL SCIENCE, 2007)
To know thyself compare thyself to others Every individual is different from another. Similarly, nations too differ from each other. International comparison between educational systems generally has a long history, although it is only recently that it has been motivated by concern for others rather than national self-interest. Comparing, of course, is one of the most basic of conscious human activities; we necessarily and constantly compare in order to make choices and to judge where we stand in relation to others and to our own past. In the more specific context of education, it is important to distinguish the comparing, importing and exporting of ideas, which is an activity intrinsic to educational development, from the task of attempting to devise rules of and procedures for doing so in a systematic way.